DNA Data Marketplace: An Analysis of the Ethical Concerns Regarding the Participation of the Individuals - Ahmed, Eman; Shabani, Mahsa (Frontiers in Genetics, 2019)
Personal genomic data and the related health data are valuable resources for both public-funded research, and for-profit entities in development of new drugs, therapies and diagnostic tests. In order to access to large datasets, pharmaceutical and biotech companies have developed partnerships with public and private entities such as Direct-to-Consumer (DTC) genetic testing companies to buy genomic and health related databases collected from research participants and customers. Although individuals mainly support data sharing for research purposes, the for-profit nature of such data sharing raises some questions regarding the rights of the data subjects and fairness in sharing benefits. In response, a new generation of sequencing and data sharing startups such as Nebula Genomics, LunaDNA and EncrypGen are emerging which aim for leaving the data control in the hands of each individual customer. In particular, such so-called “DNA data marketplaces” allow individuals to receive various types of monetary incentives to sequence their genome and share it with interested commercial parties. This paper aims to provide an exploratory and critical review of the ethical challenges related to establishing such marketplaces for genomic and health data sharing. In the view of the growing number of startups developing such marketplaces, a thorough analysis of the relevant ethical concerns is timely and needed.